Valuing Florida Water Resources: Households’ Willingness to Pay for Water Availability - Tatiana Borisova; Fei He; Xiang Bi; Kelly Grogan; Tara Wade; Syed Shah (EDIS)
This paper is a part of the EDIS series “Economic Value of Florida Water Resources”. As the other papers in the series discuss, water resources provide us with a variety of goods and services (often referred to as ecosystem services). This paper discusses another ecosystem service that Florida water resources provide: water supply for households needs. In this article, we present several examples of valuing water availability found in literature and focused on Florida and other regions.